Three-Dimensional Science Animation Implementation and Spatial Ability for Science Concept Reconstruction: A Gender-Based Education Study - Harefa, Edward; Gulo, Hardikupatu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Spatial abilities are essential to individual life and development, but gender differences in these abilities, especially in multimedia learning, are of concern. This research aims to examine the influence of gender and type of multimedia on learning outcomes in Natural Sciences (IPA) while still controlling for the influence of spatial abilities. This research uses a quantitative approach with experimental methods. The research sample consisted of 164 students. Data were collected through multivariate analysis of covariance (MANCOVA) techniques using SPSS software. Data analysis was conducted using the MANCOVA technique to test the influence of the independent variables (gender and type of multimedia) on the dependent variable (science learning outcomes) by controlling spatial ability as a covariate. Spatial ability has an overall significant influence on science learning outcomes. Boys consistently performed better than girls in all learning tasks, regardless of multimedia type. Girls also tend to prefer 3D learning media to understand science concepts. This research provides empirical evidence about the separate gender effects of spatial ability when learning using 2D static learning multimedia and 3D animation. The implication is that educational policymakers can pay attention to differences in gender preferences when choosing multimedia learning types to increase the effectiveness of science learning.